Potent therapeutic effects of ruscogenin on gastric ulcer established by acetic acid - ÇETİNEL, ŞULE (ELSEVIER SINGAPORE PTE LTD, 2020)
Background/Objective: The present study investigated the potent therapeutic effects of Ruscogenin, main steroid sapogenin of traditional Chinese plant called 'Ophiopogon japonicas', on chronic ulcer model established with acetic acid in rats. Methods: 24 rats were attenuated to the sham (2 ml/kg/day isotonic solution), control (untreated ulcer) and treatment (3 ml/kg/day ruscogenin) groups. After treatment for 2 weeks, gastric tissues were collected and prepared for light microscopic (H&E), immunohistochemical (Collagen I, III and IV) and biochemical analysis [Epidermal growth factor (EGF), Prostaglandin E2 (PGE2), Tumor Necrosis Factor alpha (TNF-alpha), Interleukin 6 and 8 (IL-6 and IL-8), Lipid Peroxidase (LPO), Myeloperoxidase (MPO), Glutathione (GSH) and Glutathione Peroxidase (GSH-Px)] and transmission electron microscopy (TEM). Results: Macroscopic scoring showed that the ulceration area of ruscogenin-treated group decreased compared with control group. Immunohistochemical analysis revealed ruscogenin ameliorated and restored the levels of Collagen I and IV to the levels of sham group. Tissue levels of EGF and PGE2 enhanced significantly in untreated ulcer group while were higher in treated ulcer group than the control group. TNF-alpha, IL-6, IL-8, LPO, MPO levels increased significantly in control group whereas decreased in treated rats after ruscogenin treatment. However, levels of GSH and GSH-Px increased significantly in treatment group. TEM showed chief cells and parietal cells of ulcer group having degenerated organelles while ruscogenin group had normal ultrastructure of cells. Conclusion: There are potent anti-inflammatory and anti-oxidant effects of ruscogenin on gastric ulcer and may be successfully used as a safe and therapeutic agent in treatment of peptic ulcer. (C) 2019 Asian Surgical Association and Taiwan Robotic Surgery Association. Publishing services by Elsevier B.V.
Keywords: Collagen; Gastric ulcer; Inflammation; Ruscogenin; Ultrastructure; DIETARY POLYPHENOLS; RUSCUS-ACULEATUS; ADHESION; DISEASE; INJURY; PATHOGENESIS; MANAGEMENT; CURCUMIN; EXTRACT; HISTORY